RANCANGAN GEOMETRI SALURAN TERBUKA DENGAN VALIDASI PEMODELAN GENANGAN SOFTWARE HEC – RAS - Bimantoro, Adyaksa Bagas; Cahyadi, Tedy Agung; Rosadi, Peter Eka; Nusanto, Gunawan; Ratminah, Wawong Dwi; Riyadi, Achmad (PERHAPI, 2024)
Open channels are a medium for collecting and channeling water to keep the mining area dry. Often there are design changes in open channel designs to suit the field, causing more time and costs. Therefore, validation is needed that can simulate the calculated open channel design before actual application. Hydrologic Engineering Center – River Analysis System (HEC-RAS) is software for simulating inundation in open channel designs to convey water before it is actually applied. The initial method used is determining the planned rainfall using the gumbell method and determining the rain catchment area (DTH) to obtain runoff discharge. The runoff discharge with three DTHs as follows, DTH I = 6.47 m3/sec, DTH II = 7.38 m3/sec, and DTH III = 10.67 m3/sec is the data to obtain open channel geometry using the Manning formula. The results of the open channel geometric design will become input data for HEC-RAS in modeling open channel inundation to validate the suitability of the design results before applying them to the field.